Heat-treatment-free aluminum alloy as well as preparation method and application thereof
By adding specific elements and limited content to the aluminum alloy, a heat-free treatment aluminum alloy with high strength, toughness and castability is prepared, which solves the problem of insufficient strength and toughness of aluminum alloy in die casting. It is suitable for large-scale integrated die casting, and Reduced costs and carbon emissions.
Patent Information
- Application Number
- CN202411268499.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the die-casting process, existing aluminum alloys have problems such as insufficient strength and toughness, easy to appear "die stick", and difficult to improve mechanical properties and thermal crack resistance at the same time, especially in large-scale integrated die-casting, and high vacuum die-casting costs, It's difficult to control.
By adding specific contents of silicon, manganese, magnesium, titanium, strontium, vanadium, zirconium and ytterbium to the aluminum alloy, and limiting the maximum content of iron, copper and zinc in the aluminum alloy, a heat-free aluminum alloy is prepared to increase its strength and tough, and suitable for large-scale integrated die casting.
It realizes the high strength, toughness, good castability, fluidity and thermal crack resistance of heat-free aluminum alloy. It is suitable for large-scale integrated die casting, and at the same time improves the tolerance of recycled aluminum to iron, reducing carbon emissions and costs. .
Smart Images

Figure CN119162492A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of aluminum alloys, and specifically relates to a heat treatment-free aluminum alloy and a preparation method and application thereof. Background Art
[0002] Aluminum alloys have the advantages of low density, high specific strength, good plasticity, certain corrosion resistance, and good machining properties. Therefore, with the rapid development of lightweight automobiles, aluminum alloys are widely used in various parts of automobiles. Traditional aluminum alloy body structural materials, such as Silafont-36 (AlSi10MnMg), need to be prepared by high vacuum die casting and subsequent T7 heat treatment processes to prepare body structural parts. However, after T7 heat treatment, the elongation and strength of Silafont-36 material are insufficient, and the riveting (SPR) process is prone to cracking; in addition, high vacuum die casting has extremely high requirements for vacuum degree, which is difficult to control and costly. Moreover, after T7 heat treatment, the product is prone to deformation, blistering and other defects. Therefore, it is very important to develop a heat-free high-strength and toughness die-casting aluminum alloy material suitable for automotive parts (especially body structural parts).
[0003] In the prior art, high-strength and tough aluminum alloy materials for die casting that do not require heat treatment include aluminum-silicon-magnesium series, aluminum-silicon series, aluminum-silicon-copper-magnesium series, and aluminum-magnesium series. The main problems currently exist are: 1) Aluminum alloy materials tend to "stick to the mold" during the die casting process. 2) Aluminum-silicon aluminum alloys have insufficient strength and toughness in the die casting state. 3) The mechanical properties and thermal cracking resistance of aluminum alloys cannot be improved at the same time. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the purpose of the present application is to propose a heat-free aluminum alloy and a preparation method and application thereof. The present application effectively improves the strength and toughness of the heat-free aluminum alloy, and at the same time makes the heat-free aluminum alloy have good castability, fluidity, and thermal cracking resistance, and is suitable for large-scale integrated die casting. At the same time, the present application can increase the iron content in the aluminum alloy to a maximum of 0.4%, thereby increasing the tolerance of recycled aluminum to iron (Fe).
[0005] In one aspect of the present application, the present application proposes a heat-treatment-free aluminum alloy. According to an embodiment of the present application, the heat-treatment-free aluminum alloy includes, by weight percentage: 6% to 9.5% silicon, 0% to 0.4% iron, 0% to 0.15% copper, 0% to 0.15% zinc, 0.2% to 0.6% manganese, 0.1% to 0.4% magnesium, 0.05% to 0.2% titanium, 0.015% to 0.025% strontium, 0.02% to 0.15% vanadium, 0.02% to 0.15% zirconium, no more than 0.1% ytterbium, and the balance is aluminum and other unavoidable impurity elements.
[0006] According to the heat-treatment-free aluminum alloy of the embodiment of the present application, by adding specific contents of silicon (Si), manganese (Mn), magnesium (Mg), titanium (Ti), strontium (Sr), vanadium (V) and zirconium (Zr) in the heat-treatment-free aluminum alloy, and by limiting the maximum contents of iron (Fe), copper (Cu) and zinc (Zn) in the aluminum alloy, the strength and toughness of the heat-treatment-free aluminum alloy are effectively improved, and the heat-treatment-free aluminum alloy has good castability, fluidity, and thermal cracking resistance, and is suitable for large-scale integrated die casting. At the same time, the present application can increase the iron content in the aluminum alloy to 0.4% at most, improve the tolerance of recycled aluminum to iron (Fe), thereby enabling more recycled aluminum to be used, greatly reducing carbon emissions and reducing costs.
[0007] In addition, the heat treatment-free aluminum alloy according to the above embodiment of the present application may also have the following additional technical features:
[0008] In some embodiments of the present application, the heat-treatment-free aluminum alloy includes: 6.5% to 9% silicon, 0.1% to 0.4% iron, 0% to 0.15% copper, 0% to 0.15% zinc, 0.2% to 0.6% manganese, 0.1% to 0.4% magnesium, 0.1% to 0.2% titanium, 0.015% to 0.025% strontium, 0.02% to 0.15% vanadium, 0.02% to 0.15% zirconium, no more than 0.1% ytterbium, and the balance is aluminum and other unavoidable impurity elements.
[0009] In some embodiments of the present application, the content of ytterbium in the heat-treatment-free aluminum alloy is 0.05% to 0.1%.
[0010] In some embodiments of the present application, the mass ratio of the vanadium to the iron is 0.05 to 0.6.
[0011] In some embodiments of the present application, the content of other unavoidable impurity elements in the heat treatment-free aluminum alloy does not exceed 0.25%.
[0012] In some embodiments of the present application, the tensile strength of the heat-treatment-free aluminum alloy is not less than 250 MPa, the yield strength of the heat-treatment-free aluminum alloy is not less than 120 MPa, and the elongation of the heat-treatment-free aluminum alloy is not less than 13%.
[0013] In a second aspect of the present application, the present application proposes a method for preparing the above-mentioned heat-treatment-free aluminum alloy. According to an embodiment of the present application, the method comprises:
[0014] (1) mixing an aluminum matrix and silicon, baking, and melting to obtain a first aluminum liquid, wherein the content of iron in the aluminum matrix is 0% to 0.4%, the content of copper in the aluminum matrix is 0% to 0.15%, and the content of zinc in the aluminum matrix is 0% to 0.15%;
[0015] (2) mixing the first aluminum liquid, the baked manganese-containing alloy, the baked titanium-containing alloy, the baked vanadium-containing alloy, the baked zirconium-containing alloy, the baked strontium-containing alloy, and magnesium metal, and melting them to obtain a second aluminum liquid;
[0016] (3) mixing the second aluminum liquid with a refining agent, refining, introducing an inert gas, removing impurities and slag, and obtaining a third aluminum liquid;
[0017] (4) detecting whether the content of each component in the third aluminum liquid meets the requirements. If it meets the requirements, proceeding to step (5); if it does not meet the requirements, adding additional elements to adjust the content of the elements in the third aluminum liquid so that the content of the elements meets the requirements;
[0018] (5) Detecting the hydrogen content in the third aluminum liquid. When the hydrogen content in the third aluminum liquid meets the requirements, high-pressure die-casting is performed on the third aluminum liquid to obtain the heat-treatment-free aluminum alloy. When the hydrogen content in the third aluminum liquid does not meet the requirements, performing step (3) until the hydrogen content in the third aluminum liquid meets the requirements.
[0019] According to the method for preparing the above-mentioned heat-free aluminum alloy in the embodiment of the present application, by adding specific contents of silicon (Si), manganese (Mn), magnesium (Mg), titanium (Ti), strontium (Sr), vanadium (V) and zirconium (Zr) in the heat-free aluminum alloy, and by limiting the maximum content of iron (Fe), copper (Cu) and zinc (Zn) in the aluminum alloy, the strength and toughness of the heat-free aluminum alloy are effectively improved, and the heat-free aluminum alloy has good castability, fluidity, and thermal cracking resistance, and is suitable for large-scale integrated die casting. At the same time, the present application can increase the iron content in the aluminum alloy to 0.4% at most, improve the tolerance of recycled aluminum to iron (Fe), thereby enabling more recycled aluminum to be used, greatly reducing carbon emissions and reducing costs.
[0020] In addition, the method for preparing heat-treatment-free aluminum alloy according to the above embodiment of the present application may also have the following additional technical features:
[0021] In some embodiments of the present application, in step (2), the first aluminum liquid, the baked manganese-containing alloy, the baked titanium-containing alloy, the baked vanadium-containing alloy, the baked zirconium-containing alloy, the baked ytterbium-containing alloy, the baked strontium-containing alloy, and magnesium metal are mixed and melted to obtain a second aluminum liquid.
[0022] In the third aspect of the present application, the present application proposes a vehicle component. According to an embodiment of the present application, the vehicle component has the heat-treatment-free aluminum alloy of the above embodiment or the heat-treatment-free aluminum alloy prepared by the method described in the above embodiment. Therefore, the vehicle component has all the advantages of the heat-treatment-free aluminum alloy of the above embodiment, specifically, the vehicle component has strong strength and toughness, and has excellent thermal cracking resistance.
[0023] In the fourth aspect of the present application, the present application proposes a vehicle. According to an embodiment of the present application, the vehicle has the vehicle components of the above embodiment. Therefore, the vehicle has all the advantages of the vehicle components of the above embodiment, which will not be repeated here.
[0024] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0026] Figure 1 200X metallographic image of the heat-treatment-free aluminum alloy prepared in Example 8 of the present application;
[0027] Figure 2 This is a SEM image of the heat-treatment-free aluminum alloy prepared in Example 8 of the present application. DETAILED DESCRIPTION
[0028] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.
[0029] This application is proposed by the inventor based on the following issues:
[0030] In the related technology, high-strength and tough aluminum alloy materials for die casting that do not require heat treatment include aluminum-silicon-magnesium series, aluminum-silicon series, aluminum-silicon-copper-magnesium series, and aluminum-magnesium series. The main problems are:
[0031] 1) Aluminum alloys tend to "stick to the mold" during the die casting process.
[0032] 2) Aluminum-silicon aluminum alloys contain a large amount of eutectic Si that crystallizes during the solidification process. The Si phase is hard and brittle, and it is easy to produce microcracks in the process of bearing loads, thereby inducing alloy fracture. Therefore, this type of material has insufficient strength and toughness in the die-cast state.
[0033] 3) Aluminum-silicon die-cast aluminum alloys contain more Fe. The solid solubility of Fe in the aluminum alloy matrix grains is extremely low. During the solidification process, it is easy to combine with Al, Si and other elements to precipitate, forming a needle-shaped hard and brittle iron-rich phase. Its needle-shaped morphology has a cutting effect on the aluminum alloy matrix grains, and stress concentration is prone to occur at the edges to form microcracks, thereby inducing alloy fracture. Therefore, the toughness of this type of material in the die-cast state is usually low.
[0034] 4) On the one hand, in order to improve the mechanical properties of aluminum alloys that do not require heat treatment, more elements such as Cu and Zn are usually added. Although this can improve the mechanical properties of aluminum alloys, it also reduces their resistance to thermal cracking. On the other hand, the increasingly large size of die-castings, coupled with their complex structures, will inevitably produce significant stress during the die-casting solidification process.
[0035] In view of this, in one aspect of the present application, the present application proposes a heat-free aluminum alloy. According to an embodiment of the present application, the heat-free aluminum alloy includes, by weight percentage: 6% to 9.5% silicon (Si), 0% to 0.4% iron (Fe), 0% to 0.15% copper (Cu), 0% to 0.15% zinc (Zn), 0.2% to 0.6% manganese (Mn), 0.1% to 0.4% magnesium (Mg), 0.05% to 0.2% titanium (Ti), 0.015% to 0.025% strontium (Sr), 0.02% to 0.15% vanadium (V), 0.02% to 0.15% zirconium (Zr), no more than 0.1% ytterbium (Yb) (and the content of ytterbium is greater than 0), and the balance is aluminum (Al) and other unavoidable impurity elements. Thus, the present application effectively improves the strength and toughness of the heat-free aluminum alloy by adding specific contents of silicon (Si), manganese (Mn), magnesium (Mg), titanium (Ti), strontium (Sr), vanadium (V), ytterbium (Yb) and zirconium (Zr) to the heat-free aluminum alloy, and by limiting the maximum contents of iron (Fe), copper (Cu) and zinc (Zn) in the aluminum alloy, and at the same time makes the heat-free aluminum alloy have good castability, fluidity, and thermal cracking resistance, and is suitable for large-scale integrated die casting. At the same time, the present application can increase the iron content in the aluminum alloy to a maximum of 0.4%, improve the tolerance of recycled aluminum to iron (Fe), thereby enabling more recycled aluminum to be used, greatly reducing carbon emissions and reducing costs.
[0036] The following is a detailed description of the principle by which the heat-treatment-free aluminum alloy proposed in this application can achieve the above beneficial effects:
[0037] In the present application, iron (Fe) is an impurity element in aluminum alloy. If its content is too high, it will affect the elongation of aluminum alloy. In the relevant technology, it is generally necessary to control the iron content below 0.15%. The present application adjusts the morphology of the iron-rich phase by adding 0.02% to 0.15% vanadium (V) and 0.2% to 0.6% manganese (Mn) to the aluminum alloy, making the needle-shaped β iron-rich phase more rounded, thereby effectively improving the elongation of the aluminum alloy. When the iron (Fe) content is 0.4%, the elongation of the aluminum alloy is not less than 13%, thereby improving the tolerance of recycled aluminum to iron (Fe), so that more recycled aluminum can be used, greatly reducing carbon emissions and reducing costs. In addition, the manganese (Mn) element can also effectively reduce product mold sticking and increase the mold life to a certain extent. Therefore, the present application can increase the iron content in the aluminum alloy to a maximum of 0.4% by adding a specific content of vanadium (V) and manganese (Mn) to the aluminum alloy. The iron content can be 0-0.4% (as an example, it can be 0, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%), which improves the tolerance of recycled aluminum to iron (Fe) and can effectively reduce the precipitation of Fe combined with elements such as Al and Si. In addition, the inventors found that if the content of vanadium (V) in the aluminum alloy is too low, the morphology of the iron-rich phase cannot be effectively controlled, thereby effectively improving the elongation of the aluminum alloy; if the content of vanadium (V) in the aluminum alloy is too high, the solid solubility of V in the α-Al matrix will reach saturation, and the refining effect of V on the alloy will no longer be enhanced. At the same time, excess V will be concentrated at the α-Al dendrite boundary of the alloy to form a low-melting eutectic phase, resulting in reduced mechanical properties of the alloy; if the content of manganese (Mn) in the aluminum alloy is too low, the morphology of the iron-rich phase cannot be effectively controlled, thereby effectively improving the elongation of the aluminum alloy; if the content of manganese (Mn) in the aluminum alloy is too high, a large amount of α-Fe phase will be formed, which will seriously reduce the toughness of the alloy.
[0038] At the same time, the present application can make the aluminum alloy microstructure distribution more uniform and the α-Al grains finer by adding 0.02% to 0.15% zirconium (Zr) to the aluminum alloy, thereby effectively improving the strength and toughness of the aluminum alloy. And the addition of the Zr element can increase the stability of the material properties. The inventors found that if the zirconium (Zr) content in the aluminum alloy is too low, it will lead to the inability to effectively make the microstructure distribution more uniform, thereby failing to effectively improve the strength and toughness of the aluminum alloy, and failing to effectively improve the stability of the material properties; if the zirconium (Zr) content in the aluminum alloy is too high, a Zr-rich phase will be formed, affecting the toughness of the material.
[0039] In addition, the aluminum alloy of the present application contains 0.015% to 0.025% strontium (Sr), and strontium is used to modify eutectic silicon, spheroidizing the lamellar eutectic silicon, further ensuring the toughness of the aluminum alloy, that is, improving the elongation of the aluminum alloy. The inventors found that if the content of strontium (Sr) in the aluminum alloy is too low, the eutectic silicon cannot be effectively modified, and thus the elongation of the aluminum alloy cannot be effectively improved; if the content of strontium (Sr) in the aluminum alloy is too high, the phenomenon of metamorphism and decay will occur, making the metamorphism effect of the eutectic silicon not obvious, affecting the toughness of the material.
[0040] In the present application, both copper (Cu) and zinc (Zn) have the effect of improving the strength of aluminum alloy, but at the same time reduce its thermal cracking resistance. Therefore, the present application limits the content of copper (Cu) to 0% to 0.15% and the content of zinc (Zn) to 0% to 0.15%, so that the aluminum alloy has good castability, fluidity, and thermal cracking resistance, and is suitable for large-scale integrated die casting.
[0041] In the present application, the aluminum alloy of the present application contains 6% to 9.5% silicon (Si), which can effectively improve the castability and fluidity of the aluminum alloy, and at the same time effectively improve the strength of the aluminum alloy. The inventors found that if the content of silicon (Si) in the aluminum alloy is too low, it will lead to the inability to effectively ensure the castability and fluidity of the aluminum alloy, and at the same time, it will not be able to effectively improve the strength of the aluminum alloy; if the content of silicon (Si) in the aluminum alloy is too high, the tensile strength and hardness of the alloy will increase, but the toughness will also decrease significantly, making the material more prone to fracture.
[0042] At the same time, the aluminum alloy of the present application contains 0.1% to 0.4% magnesium (Mg), and Mg and Si will form a Mg2Si strengthening phase, thereby effectively improving the strength of the aluminum alloy. The inventors found that if the content of magnesium (Mg) in the aluminum alloy is too low, the Mg2Si strengthening phase cannot be effectively formed, thereby failing to effectively improve the strength of the aluminum alloy; if the content of magnesium (Mg) in the aluminum alloy is too high, the toughness and elongation of the aluminum alloy will be reduced.
[0043] In addition, the aluminum alloy of the present application also includes 0.05% to 0.2% titanium (Ti), which can effectively refine and regulate the microstructure, thereby effectively improving the strength and elongation of the aluminum alloy. The inventors have found that if the content of titanium (Ti) in the aluminum alloy is too low, it will lead to the inability to effectively refine and regulate the microstructure, thereby effectively improving the strength and elongation of the aluminum alloy; if the content of titanium (Ti) in the aluminum alloy is too high, it will form Ti-rich phases (TiAl3, Ti(AlSi)2, Ti2Si3Al, Ti7Si 12 A l5These Ti-rich phases are mostly hard and brittle, and can weaken the matrix by passing through the α-Al grains, resulting in a sharp drop in the plasticity of the alloy.
[0044] In addition, the aluminum alloy of the present application also includes: no more than 0.1% ytterbium Yb (and the ytterbium content is greater than 0), and the rare earth element Yb can optimize the organizational structure of the aluminum alloy, stabilize the grain boundary, and avoid the phenomenon of discontinuous distribution of the grain boundary, thereby further improving the strength and toughness of the aluminum alloy. At the same time, it can also increase the corrosion resistance of the aluminum alloy.
[0045] In summary, the present application effectively improves the strength and toughness of the heat-free aluminum alloy by adding specific contents of silicon (Si), manganese (Mn), magnesium (Mg), titanium (Ti), strontium (Sr), vanadium (V), ytterbium (Yb) and zirconium (Zr) in the heat-free aluminum alloy, and by limiting the maximum content of iron (Fe), copper (Cu) and zinc (Zn) in the aluminum alloy, and at the same time makes the heat-free aluminum alloy have good castability, fluidity, and thermal cracking resistance, which is suitable for large-scale integrated die casting. Specifically, the tensile strength of the heat-free aluminum alloy can be not less than 250MPa, the yield strength can be not less than 120MPa, and the elongation can be not less than 13%. At the same time, the present application can increase the iron content in the aluminum alloy to 0.4%, which increases the tolerance of recycled aluminum to iron (Fe), thereby enabling more use of recycled aluminum, greatly reducing carbon emissions and reducing costs.
[0046] As some preferred embodiments, the heat-free aluminum alloy includes, by weight percentage: 6.5% to 9% silicon (as an example, it can be 6.5%, 6.8%, 7%, 7.2%, 7.5%, 7.8%, 8%, 8.2%, 8.5%, 8.7%, 9% silicon), 0.1% to 0.4% iron (as an example, it can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4% iron), 0% to 0.15% copper ( As examples, it can be 0%, 0.02%, 0.05%, 0.08%, 0.1%, 0.12%, 0.15% copper), 0% to 0.15% zinc (as examples, it can be 0%, 0.02%, 0.05%, 0.08%, 0.1%, 0.12%, 0.15% zinc), 0.2% to 0.6% manganese (as examples, it can be 0.2%, 0.3%, 0.4%, 0.42%, 0.45%, 0.48%, 0.5%, 0.52%, 0.63%, 0.64%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 0.99%, 0.99%, 0.99%, .55%, 0.58%, 0.6% manganese), 0.1% to 0.4% magnesium (as an example, it can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4% magnesium), 0.1% to 0.2% titanium (as an example, it can be 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2% titanium), 0.015% to 0.025% strontium (as an example, it can be 0.015%, 0.017%) , 0.020%, 0.022%, 0.025% strontium), 0.02% to 0.15% vanadium (as an example, it can be 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.12%, 0.15% vanadium), 0.02% to 0.15% zirconium (as an example, it can be 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.12%, 0.15% zirconium), no more than 0.25% impurities, and the balance is aluminum. By limiting the content of each component within the above range, the strength and toughness of the heat-free aluminum alloy are further effectively improved, and the heat-free aluminum alloy is further made to have good castability, fluidity, and thermal cracking resistance, and is suitable for large-scale integrated die casting.
[0047] As some preferred embodiments, the ytterbium content in the above-mentioned heat-treatment-free aluminum alloy is 0.05% to 0.1%, and as examples it can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, etc., thereby further improving the strength and toughness of the aluminum alloy and further increasing the corrosion resistance of the aluminum alloy.
[0048] According to some further specific embodiments of the present application, the mass ratio of the vanadium to the iron is 0.05-0.6, and can be 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, etc. By limiting the mass ratio of vanadium to the iron within the above range and by compositely adding Mn to form a multi-phase, the organizational morphology and phase distribution of the aluminum alloy can be significantly improved, and the coarse needle-shaped Al3Fe phase can be transformed into a fine spherical Al-(Fe, V, Mn)-Si phase, thereby effectively improving the elongation of the aluminum alloy.
[0049] In an embodiment of the present application, the content of other inevitable impurity elements in the heat-treatment-free aluminum alloy does not exceed 0.25%. The above-mentioned other impurities refer to impurities other than iron (Fe), copper (Cu) and zinc (Zn). Specifically, the above-mentioned other impurities include but are not limited to at least one of chromium, phosphorus, calcium, molybdenum, etc. Further, the content of other single element impurities in the heat-treatment-free aluminum alloy does not exceed 0.05%, for example, the content of chromium impurities does not exceed 0.05% or the content of phosphorus impurities does not exceed 0.05%, etc. Thereby, the strength and toughness of the aluminum alloy are further ensured.
[0050] According to some specific embodiments of the present application, the tensile strength of the heat-free aluminum alloy is not less than 250 MPa, the yield strength of the heat-free aluminum alloy is not less than 120 MPa, and the elongation of the heat-free aluminum alloy is not less than 13%. That is, the heat-free aluminum alloy of the present application has high tensile strength, yield strength and elongation.
[0051] In a second aspect of the present application, the present application proposes a method for preparing the above-mentioned heat-treatment-free aluminum alloy. According to an embodiment of the present application, the method comprises:
[0052] S100: mixing, baking and melting the aluminum matrix and silicon to obtain a first aluminum liquid;
[0053] In this step, the aluminum matrix and silicon are mixed, baked, and melted to obtain the first aluminum liquid, the iron content in the aluminum matrix is 0-0.4% (the iron content in the aluminum matrix can be 0), the copper content in the aluminum matrix is 0%-0.15% (the copper content in the aluminum matrix can be 0), and the zinc content in the aluminum matrix is 0%-0.15% (the zinc content in the aluminum matrix can be 0).
[0054] As some specific embodiments, the melting furnace can be gradually heated up to bake out the water vapor in the furnace. During the heating process, a certain proportion of aluminum matrix (such as A00) and silicon are placed on the side of the furnace for baking. After baking for 20 to 40 minutes, the aluminum matrix (such as A00) and silicon are put into the furnace and heated up to melt. The furnace temperature is set at 720 degrees Celsius to 800 degrees Celsius.
[0055] S200: mixing and melting the first aluminum liquid, the baked manganese-containing alloy, the baked titanium-containing alloy, the baked vanadium-containing alloy, the baked zirconium-containing alloy, the baked strontium-containing alloy, and magnesium metal to obtain a second aluminum liquid;
[0056] According to some specific embodiments of the present application, a first aluminum liquid, a baked manganese-containing alloy, a baked titanium-containing alloy, a baked vanadium-containing alloy, a baked zirconium-containing alloy, a baked ytterbium-containing alloy, a baked strontium-containing alloy, and magnesium metal are mixed and melted to obtain a second aluminum liquid.
[0057] As some specific embodiments, manganese-containing alloys (such as AlMn10), titanium-containing alloys (such as AlTi10), vanadium-containing alloys (such as AlV10), zirconium-containing alloys (such as AlZr10), and ytterbium-containing alloys (such as AlYb10) can be placed on the side of a furnace for baking, and then put into the furnace after baking for 20 to 40 minutes. They can be put into the furnace several times, stirred, and fully melted. Then, a bell jar can be used to press the pure Mg block into the aluminum liquid and fully melt it. After standing still for 20 to 40 minutes, a strontium-containing alloy (such as AlSr10) is put into the aluminum liquid and fully melted to obtain a second aluminum liquid.
[0058] S300: mixing the second aluminum liquid with a refining agent, refining, introducing an inert gas, removing impurities and slag, and obtaining a third aluminum liquid;
[0059] In this step, a mobile rotary degasser can be used to press the aluminum alloy refining agent into the second aluminum liquid for refining to improve the purity of the aluminum alloy liquid. Then an inert gas (such as 99.999% argon) is introduced to remove the gas in the second aluminum liquid. Finally, the slag is removed to remove the impurities and the slag is left to stand to obtain the third aluminum liquid.
[0060] According to some specific embodiments of the present application, the mass of the refining agent is 0.1%-0.2% of the mass of the second aluminum liquid. In the embodiments of the present application, the specific type of the refining agent is not particularly limited, and those skilled in the art can select it according to actual needs, such as a sodium-free refining agent.
[0061] S400: Check whether the content of each component in the third aluminum liquid meets the requirements;
[0062] In this step, an electric spark direct reading spectrometer can be used to detect whether the content of each component in the third aluminum liquid meets the requirements. If it does, step S500 is performed; if it does not meet the requirements, additional elements are added to adjust the content of the element in the third aluminum liquid so that the content of the element meets the requirements, that is, reaches the preset mass percentage of the element in the aluminum alloy.
[0063] S500: detecting the hydrogen content in the third aluminum liquid;
[0064] In this step, a hydrogen meter can be used to detect the hydrogen content in the third aluminum liquid. When the hydrogen content in the third aluminum liquid meets the requirements, the third aluminum liquid is subjected to high pressure die casting to obtain a heat-free aluminum alloy. When the hydrogen content in the third aluminum liquid does not meet the requirements, step S300 is performed until the hydrogen content in the third aluminum liquid meets the requirements. As some specific embodiments, when the hydrogen content is less than 0.15ml / 100g, the third aluminum liquid can be cast into a mold using high pressure die casting equipment. If the hydrogen content does not meet the requirements, the refining and degassing in step S300 should be continued.
[0065] As some specific embodiments, the third aluminum liquid can be high-pressure die-casted by a LJ 280T die-casting machine equipped with a vacuum system, an oil circulation mold temperature controller, and a barrel heating device to prepare a 3mm×80mm×200mm flat mold test piece. The process parameters of high-pressure casting are as follows: mold cavity vacuum ≤50Mbar, injection speed 2.5±0.5m / s, mold temperature 130±10℃, and the temperature of the third aluminum liquid is 680±10℃.
[0066] As some specific embodiments, the mechanical properties of the heat-free aluminum alloy can be measured by using a Sansi tensile machine and an imported extensometer, with a tensile rate of 1 mm / s. The specimens for the tensile test are processed strictly in accordance with the specimens in GB / T228.1 2010.
[0067] According to the method for preparing the above-mentioned heat-free aluminum alloy in the embodiment of the present application, by adding specific contents of silicon (Si), manganese (Mn), magnesium (Mg), titanium (Ti), strontium (Sr), vanadium (V), zirconium (Zr) and ytterbium (Yb) in the heat-free aluminum alloy, and by limiting the maximum content of iron (Fe), copper (Cu) and zinc (Zn) in the aluminum alloy, the strength and toughness of the heat-free aluminum alloy are effectively improved, and the heat-free aluminum alloy has good castability, fluidity, and thermal cracking resistance, and is suitable for large-scale integrated die casting. At the same time, the present application can increase the iron content in the aluminum alloy to 0.4% at most, improve the tolerance of recycled aluminum to iron (Fe), thereby enabling more recycled aluminum to be used, greatly reducing carbon emissions and reducing costs.
[0068] In the third aspect of the present application, the present application proposes a vehicle component. According to an embodiment of the present application, the vehicle component has the heat-treatment-free aluminum alloy of the above embodiment or the heat-treatment-free aluminum alloy prepared by the method described in the above embodiment. Therefore, the vehicle component has all the advantages of the heat-treatment-free aluminum alloy of the above embodiment, specifically, the vehicle component has strong strength and toughness, and has excellent thermal cracking resistance.
[0069] In particular, the vehicle component may be a vehicle body structural component.
[0070] In the fourth aspect of the present application, the present application proposes a vehicle. According to an embodiment of the present application, the vehicle has the vehicle components of the above embodiment. Therefore, the vehicle has all the advantages of the vehicle components of the above embodiment, which will not be repeated here.
[0071] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.
[0072] Example 1
[0073] The present embodiment provides a heat-treatment-free aluminum alloy, which includes, by weight percentage, 7.9% silicon, 0.25% iron, 0.08% copper, 0.08% zinc, 0.4% manganese, 0.3% magnesium, 0.15% titanium, 0.020% strontium, 0.10% vanadium, 0.10% zirconium, 0.05% ytterbium, and other impurities not exceeding 0.25%, and the balance is aluminum. The specific contents are shown in Table 1.
[0074] And prepare high-strength and toughness heat-treatment-free aluminum alloy castings according to the following steps:
[0075] Step 1: First, gradually heat up the melting furnace to bake out the water vapor in the furnace. During the heating process, place the aluminum matrix A00 and silicon in the above proportion on the side of the furnace for baking. After baking for 30 minutes, put the aluminum matrix A00 and silicon into the furnace, heat up and melt. The aluminum liquid temperature is set to 720 degrees Celsius and the furnace temperature is set to 780 degrees Celsius.
[0076] Step 2: After A00 and silicon are dissolved, first place AlFe20, AlMn10, AlTi10, AlV10, AlZr10, and optional AlYb10 master alloys on the side of the furnace for baking. After baking for 30 minutes, put them into the furnace, put them into the furnace several times, stir, and fully melt. Then use a bell jar to press the pure Mg block into the aluminum liquid and fully melt it. After standing for 30 minutes, put the AlSr10 master alloy into the aluminum liquid and fully melt it.
[0077] A mobile rotary degasser is used to press a sodium-free refining agent of aluminum alloy into the aluminum liquid for refining, and the mass of the refining agent is 0.15% of the mass of the aluminum liquid. Then 99.999% argon is introduced for 15 minutes of degassing, and then the slag is removed and allowed to stand.
[0078] Step 3: Use an electric spark direct reading spectrometer to detect whether the aluminum alloy composition meets the use standard. If so, proceed to step 4. If not, it means that the mass percentage of a certain element in the aluminum alloy liquid does not reach the above-mentioned preset mass percentage, and additional elements need to be added to adjust the mass percentage of the element in the aluminum alloy liquid so that the element denies the mass percentage and meets the use standard, that is, reaches the preset mass percentage.
[0079] Step 4: Detect the gas content by a hydrogen meter, and when the hydrogen content is less than 0.15ml / 100g, die-cast it by high-pressure die-casting equipment. If the gas content does not meet the standard, continue with the refining and degassing in step 2.
[0080] Step 5: High pressure die casting was performed by LK 280T die casting machine, which was equipped with vacuum system, oil circulation mold temperature controller, and barrel heating device to prepare a 3mm×80mm×200mm flat mold test piece. The process parameters of high pressure casting are as follows: mold cavity vacuum ≤50Mbar, injection speed 2.5±0.5m / s, mold temperature 130±10℃, aluminum alloy liquid temperature 680±10℃.
[0081] Step 6: The mechanical properties are measured by Sansi tensile testing machine and imported extensometer, with a tensile rate of 1 mm / s. The specimens for the tensile test are processed strictly in accordance with the specimens in GB / T228.1 2010.
[0082] Example 2 to Example 11
[0083] The preparation methods of Examples 2 to 11 are basically the same as those of Example 1, the only difference being the content of each component of the heat-treatment-free aluminum alloy, as shown in Table 1.
[0084] Comparative Example 1 to Comparative Example 7
[0085] The preparation methods of Comparative Examples 1 to 7 are basically the same as those of Example 8, and the only difference is the content of each component of the heat-treatment-free aluminum alloy, as shown in Table 1.
[0086] Table 1
[0087]
[0088]
[0089] The mechanical properties of the samples of Examples 1 to 11 and Comparative Examples 1 to 7 were measured by a Sansi tensile machine and an imported extensometer, respectively, with a tensile rate of 1 mm / s. The samples for the tensile test were processed strictly in accordance with the samples in GB / T228.1 2010. The results are shown in Table 2.
[0090] Table 2
[0091] Tensile strength(MPa) Yield strength(MPa) Elongation(%) Example 1 274 128 13.8 Example 2 278 130 14.3 Example 3 283 133 14.6 Example 4 286 136 15.0 Example 5 266 120 16.0 Example 6 268 122 15.5 Example 7 270 123 15.2 Example 8 275 125 14.8 Example 9 280 135 13.8 Example 10 283 137 13.5 Embodiment 11 285 139 13.2 Comparative Example 1 265 110 12.6 Comparative Example 2 273 123 11.7 Comparative Example 3 230 100 10.4 Comparative Example 4 290 145 12.7 Comparative Example 5 268 115 12.0 Comparative Example 6 270 123 10.5 Comparative Example 7 260 118 11.8
[0092] As can be seen from Table 2, compared with Comparative Example 1, the tensile strength, yield strength and elongation of Example 8 are significantly improved. It can be seen that by adding a specific content of zirconium (Zr) to the aluminum alloy, the tensile strength, yield strength and elongation of the aluminum alloy can be effectively improved.
[0093] It can be seen from Table 2 that compared with Comparative Example 2, the elongation of Example 8 is significantly improved. It can be seen that by adding a specific content of vanadium (V) to the aluminum alloy, the elongation of the aluminum alloy can be effectively improved.
[0094] It can be seen from Table 2 that compared with Example 8, the tensile strength and yield strength of Comparative Example 3 are significantly reduced. It can be seen that if the silicon (Si) content in the aluminum alloy is too low, it will lead to the inability to effectively improve the strength of the aluminum alloy, and at the same time, it will be impossible to effectively ensure the castability and fluidity of the aluminum alloy.
[0095] It can be seen from Table 2 that compared with Example 8, the elongation of Comparative Example 4 is significantly reduced. It can be seen that if the content of magnesium (Mg) in the aluminum alloy is too high, the toughness and elongation of the aluminum alloy will be reduced.
[0096] It can be seen from Table 2 that compared with Example 8, the tensile strength, yield strength and elongation of Comparative Example 5 are significantly reduced. It can be seen that if the zirconium (Zr) content in the aluminum alloy is too low, it will lead to the inability to effectively improve the strength and toughness of the aluminum alloy, and at the same time, it will not be able to effectively improve the stability of the material properties.
[0097] It can be seen from Table 2 that compared with Example 8, the elongation of Comparative Example 6 is significantly reduced. It can be seen that if the content of strontium (Sr) in the aluminum alloy is too low, the elongation of the aluminum alloy cannot be effectively improved.
[0098] It can be seen from Table 2 that compared with Example 8, the tensile strength, yield strength and elongation of Comparative Example 7 are significantly reduced. It can be seen that if the content of titanium (Ti) in the aluminum alloy is too low, it will lead to the inability to effectively improve the strength and elongation of the aluminum alloy.
[0099] Figure 1 200X metallographic image of the heat-treatment-free aluminum alloy prepared in Example 8 of the present application; Figure 2 This is a SEM image of the heat-treatment-free aluminum alloy prepared in Example 8 of the present application. Figure 1 and attached Figure 2 It can be seen that the material has uniform tissue distribution, small and round grains, and no obvious segregation and abnormal alloy phase, which shows that the composition design is reasonable, the microstructure is good, and the material strength and toughness can be taken into account at the same time.
[0100] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0101] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A heat-treatment-free aluminum alloy, It is characterized in that Calculated in percentage by weight, it includes: 6% to 9.5% silicon, 0% to 0.4% iron, 0% to 0.15% copper, 0% to 0.15% zinc, 0.2% to 0.6% manganese, 0.1% to 0.4% magnesium, 0.05% to 0.2% titanium, 0.015% to 0.025% strontium, 0.02% to 0.15% vanadium, 0.02% to 0.15% zirconium, not more than 0.1% ytterbium, and the balance is aluminum and other unavoidable impurity elements.
2. The heat-treatment-free aluminum alloy according to claim 1, It is characterized in that include: 6.5% to 9% silicon, 0.1% to 0.4% iron, 0% to 0.15% copper, 0% to 0.15% zinc, 0.2% to 0.6% manganese, 0.1% to 0.4% magnesium, 0.1% to 0.2% titanium, 0.015% to 0.025% strontium, 0.02% to 0.15% vanadium, 0.02% to 0.15% zirconium, not more than 0.1% ytterbium, the balance is aluminum and other unavoidable impurity elements.
3. The heat-treatment-free aluminum alloy according to claim 1, It is characterized in that The content of ytterbium in the heat treatment-free aluminum alloy is 0.05% to 0.1%.
4. The heat-treatment-free aluminum alloy according to claim 1, It is characterized in that The mass ratio of the vanadium to the iron is 0.05 to 0.
6.
5. The heat-treatment-free aluminum alloy according to claim 1, It is characterized in that The content of other inevitable impurity elements in the heat-treatment-free aluminum alloy does not exceed 0.25%.
6. The heat-treatment-free aluminum alloy according to any one of claims 1 to 5, It is characterized in that The tensile strength of the heat-treatment-free aluminum alloy is not less than 250 MPa, the yield strength of the heat-treatment-free aluminum alloy is not less than 120 MPa, and the elongation of the heat-treatment-free aluminum alloy is not less than 13%.
7. A method for preparing the heat-treatment-free aluminum alloy according to any one of claims 1 to 6, It is characterized in that include: (1) mixing an aluminum matrix and silicon, baking, and melting to obtain a first aluminum liquid, wherein the content of iron in the aluminum matrix is 0% to 0.4%, the content of copper in the aluminum matrix is 0% to 0.15%, and the content of zinc in the aluminum matrix is 0% to 0.15%; (2) mixing the first aluminum liquid, the baked manganese-containing alloy, the baked titanium-containing alloy, the baked vanadium-containing alloy, the baked zirconium-containing alloy, the baked strontium-containing alloy, and magnesium metal, and melting them to obtain a second aluminum liquid; (3) mixing the second aluminum liquid with a refining agent, refining, introducing an inert gas, removing impurities and slag, and obtaining a third aluminum liquid; (4) detecting whether the content of each component in the third aluminum liquid meets the requirements. If it meets the requirements, proceeding to step (5); if it does not meet the requirements, adding additional elements to adjust the content of the elements in the third aluminum liquid so that the content of the elements meets the requirements; (5) Detecting the hydrogen content in the third aluminum liquid. When the hydrogen content in the third aluminum liquid meets the requirements, high-pressure die-casting is performed on the third aluminum liquid to obtain the heat-treatment-free aluminum alloy. When the hydrogen content in the third aluminum liquid does not meet the requirements, performing step (3) until the hydrogen content in the third aluminum liquid meets the requirements.
8. The method according to claim 7, It is characterized in that In step (2), the first aluminum liquid, the baked manganese-containing alloy, the baked titanium-containing alloy, the baked vanadium-containing alloy, the baked zirconium-containing alloy, the baked ytterbium-containing alloy, the baked strontium-containing alloy, and magnesium metal are mixed and melted to obtain a second aluminum liquid.
9. A vehicle component, It is characterized in that A heat-treatment-free aluminum alloy according to any one of claims 1 to 6 or a heat-treatment-free aluminum alloy prepared by the method according to claim 7 or 8.
10. A vehicle, It is characterized in that A vehicle component according to claim 9.
Citation Information
Patent Citations
Heat-treatment-free high-toughness die-casting aluminum alloy as well as preparation method and product thereof
CN115961183A
Aluminum alloy and preparation method thereof, casting and preparation method thereof, and vehicle
CN117965969A
